وحيية السنة عند الحداثيين – دراسة نقدية - العقون, مريم (University of Eloued جامعة الوادي, 2017)
يتناول هذا البحث موضوع وحيية السنة عند الحداثيين دراسة نقدية، حيث يتكلم عن إنكارهم لوحيية السنة ونسبوا إليها شبهات وأباطيل لا تليق وبهذا الصدد سنقوم في المبحث الأول بالتعريف بمفهوم الحداثة ونشأتها، وذكر بعض أعلامها وموقفهم من السنة النبوية، ومنطلقاتهم للطعن فيها. ثم ينطلق بعدها حديثنا في المبحث الثاني عن السنة مفهومها في شرعنا، وعند الحداثيين، وتفكيكهم لحجيتها. وبعدها المبحث الثالث الذي كان الكلام فيه مثله مثل المبحث الذي يسبقه لكن بدل السنة الوحي،. ليكون بالمبحث الأخير بعض ما قاله الحداثيون لإنكار صفة الوحي عن السنة النبوية وكذا قولهم بأنسنتها وذلك بنسبتها لإنساني عادي، ثم الكلام عن تاريخيتها وإنكار ثبوا في التاريخ الإسلامي. This search is a critic study about the revelatory of the Sunnah in the point view of the modernism, as this research points to their denial to the revelatory of the Sunnah and they covered it with suspicions and doubts that have nothing to do with it, hence in the first chapter of this research we intend to clarify the definition of the modernism and its growth, as well as some of its main figures and their attitudes towards the Sunnah, and their principles, arguments and reasons to deny it, then we shall talk in the second chapter about the Sunnah and its definition in Sharia'h and in the revelatory 's point of view, and their complete denial to it, as for the third chapter, it will be like the one before, but it will be about the revelation instead of Sunnah, and in the last chapter, there will be some statements by the revelatory about Sunnah and revelation .
مذكرة ماستر تخصص علوم حديث
Keywords: الحداثة – السنة – الوحي; Alhadatha – Alsonna - Revelation